Minimally invasive endoscopic treatment for pediatric combined high grade stenosis as a laryngeal manifestation of epidermolysis bullosa - Pálinkó Dóra (INTERNATIONAL JOURNAL OF PEDIATRIC OTORHINOLARYNGOLOGY, 2017)
Epidermolysis bullosa refers to a clinically and genetically heterogeneous group of inherited mucocutaneous diseases. Laryngotracheal lesions are momentous regarding the risk of sudden airway obstruction. The traditional treatment is tracheostomy. This case report highlights the advantages of minimally invasive interventions. A successful combined endoscopic management of a life-threatening respiratory crisis is presented in a 4-year-old child. Combined commissure stenosis with supraglottic spread was treated by CO2 laser dissection and bilateral endoscopic arytenoid abduction lateropexy, supplemented with mitomycin C application. Due to expectable less scarring, the combination of these modern methods may be an efficient solution in these vulnerable respiratory tracts.